2015
DOI: 10.5539/ijbm.v10n8p151
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Management Process in Jordanian Public Shareholding Organisations

Abstract: Risk management, as a business practice in developing and emerging nations, is an under-researched area. The aim of this paper is to contribute to the development of risk management theory and practice by examining the determinants of the integration of risk management within public shareholding organizations in an Arab country, Jordan.A survey strategy was used and questionnaires were distributed to Jordanian organizations listed on the Amman Stock Exchange. Parametric statistics such as Pearson's correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…In the context of the Middle East, the events of the Arab Spring have increased the risk perceptions of organizations (Al Khattab & Hood, 2015). Previous risk management studies on Jordanian organizations (Khattab, Anchor, & Davies, 2008) reported that risk assessment practice is crisis-oriented.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the Middle East, the events of the Arab Spring have increased the risk perceptions of organizations (Al Khattab & Hood, 2015). Previous risk management studies on Jordanian organizations (Khattab, Anchor, & Davies, 2008) reported that risk assessment practice is crisis-oriented.…”
Section: Introductionmentioning
confidence: 99%